Using Differentiation Strategies for Gifted Pupils in Primary School Science Classes - Letina, Alena (Revija za elementarno izobraževanje, 2021)
The aim of this study was to determine the extent to which gifted pupils receive differentiated instruction in primary school science classes, which of the differentiated instruction strategies are used by teachers and how often. The survey sample included 134 primary school teachers. The results show that teachers frequently use questioning and thinking activities but make only minor modifications in the regular curriculum to meet the needs of gifted pupils. Gifted pupils rarely engage in activities such as providing challenges and choices, differentiated reading and writing assignments, individually set work, activities involving curriculum modification, and enrichment centres.